Pengaruh Persepsi Bagi Hasil, Promosi, Dan Kualitas Pelayanan Perbankan Syariah Terhadap Minat Nasabah Dalam Menggunakan Tabungan Mudharabbah (Studi Kasus Pada Mahasiswa UNISMA) - Berliana Farah Annisa; Noor Shodiq Askandar; Afifudin Afifudin (El-Aswaq, 2021)
This study aims to determine the effect of perceptions of profit sharing, promotion,and service quality on customer interest in using mudharabbah savings. Thepopulation in this study were students majoring in Islamic banking, FEB UNISMA,2017, 2018, and 2019 totaling 252 people. The number of samples in this study usedpurposive sampling. The analytical tool used is multiple linear regression analysisusing SPSS 25. The results of this study indicate that the variables for profit sharing(X1), promotion (X2), and service quality (X3) have a significant positive effectsimultaneously on customer interest (Y).